PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II KENDARI - Agus Rahman; Buyung Sarita; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this study is to examine and analyze the effect of competence and non-physical work environment on job satisfaction and employee performance, examine the effect of job satisfaction on employee performance, and examine the mediating effect of job satisfaction on the influence of competence and non-physical work environment on employees performance at Child Special Development Institution Class II Kendari. This research approach is quantitative using survey methods and explanatory research design. The data was collected by cross-section using an instrument of a questionnaire. The population on this study were employees at Child Special Development Institution Class II Kendari, using the census method of determining respondents, so that the respondent size was set at 46 employees. The analytical tool used is Partial Least Square (PLS).The results of this study indicate that competence has a positive and significant effect on employee performance. competence has a positive and significant effect on job satisfaction, non-physical work environment has a positive and significant effect on employee performance, non-physical work environment has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and job satisfaction does not mediate the effect of competence and non-physical work environment on employee performance. From these results it can be concluded that the better the competence possessed, the existing non-physical work environment and also the perceived job satisfaction, will be able to improve employee performance.